Perception of the office of the taxi Ombud in South Africa: consumer based brand equity approach - Seopela, Pearl (My University, 2019)
The area of the Ombud in South Africa has not received much attention and the issue of brand equity has not been prominent or widely covered in the finance, tax and accounting industry. The Office of the Tax Ombud, as a tax brand, has a role to play in the finances of individual taxpayers and business entities. The Tax Ombud in South Africa is fairly new and has only been in existence for five years. An awareness and understanding of the existence of the Office of the Tax Ombud plays an important role in assisting to enhance the knowledge of consumers in understanding their rights and obligations, and also has the potential to improve effective tax compliance. It is therefore important that marketing managers in the Office of the Tax Ombud make their customers familiar with its offering (brand awareness) in order to create and maintain brand associations that are strong, favourable and unique when compared to other brands with offerings in the same category (brand image) (O'Cass & Grace, 2004). The purpose of this study was to focus on the consumer/taxpayer perspective of consumer-based brand equity of the Ombud brand, where the four dimensions of Aaker’s (1991) model, namely brand awareness, brand association, brand loyalty and perceived quality for the Office of the Tax Ombud, were explored. It will contribute to filling the gap in brand equity associated with service industries (Krishnan & Hartline, 2001); as most of the available literature has been based on tangible brands (Brahmbhatt & Shah, 2017). To date, service brands have not been accorded sufficient research attention (O'Cass & Grace, 2004). This was earlier argued by Krishnan and Hartline (2001), who stated that what is known about brand equity for services brands is based on theoretical or anecdotal evidence, which suggests that a basic understanding of the nature of brand equity for services has yet to emerge. The study intends to make a contribution towards the context of service brand equity, and tax brand equity in particular, where literature is limited. The research hypotheses explored the perception of the Office of the Tax Ombud in relation to Aaker’s (1991) model of consumer-based brand equity (CBBE) dimensions, namely, brand awareness, brand association, brand loyalty and perceived quality. A sample of 531 respondents was used to evaluate the consumer-based approach. The research methodology for the study was built on previous research on brand equity conceptualisation that was used on the same determined dimensions of the Aaker (1991a), or Keller’s (1993b), theoretical models. The quantitative study was conducted and information was gathered through a cross sectional survey. The selfadministered questionnaire was electronically distributed to respondents through an email which had a link. The survey was sent to 10 165 participants of community panel members from the Consulta agency which has a community database that allows the general consumer a safe, but true, platform to contribute to the total offering package of day-to-day consumer products and services, by voicing their opinion and participating in surveys and research activities. In addition, the questionnaire was randomly distributed to tax professionals through their recognised controlling bodies. The survey was completed by 531 respondents. The questionnaire consisted of independent variables (brand awareness, brand association, brand loyalty and perceived quality) and a dependent variable (brand equity) which were adopted from the previous work of Aaker’s (1991) model of brand equity. The following hypotheses were used and conclusions reached: Hypothesis 1: Greater awareness of the Office of the Tax Ombud will have a positive and significant impact on brand equity. According to the results of the study, there is no statistically significant relationship between the brand awareness and the brand equity. The results indicate that brand awareness does not drive brand equity and therefore does not support hypothesis 1. Therefore, it is recommended that the Office of the Tax Ombud should use designed targeted marketing and communication activities to promote a high level of brand awareness and a positive brand image that will enhance brand choice, as well as brand loyalty and positively influence brand association, perceived quality and brand equity, (Alexandra & Cerchia, 2018). In addition, extensive research can be done to measure brand awareness due to its importance for assisting marketing managers to reinforce consistent marketing activities to maintain its brand continuity, Keller (2003). Hypothesis 2: The brand association of the Office of the Tax Ombud with fairness will have positive and significant impact on brand equity. The results displayed a positive and significant relationship between the brand association and brand equity. The results indicate that brand association drives brand equity and therefore supports hypothesis 2. Accordingly, when consumers associate the Office of the Tax Ombud with fairness based on their experience and the attittude of its employees, higher brand equity will be promoted (Yoo, Donthu, & Lee, 2000). It is therefore important that brand managers focus on targeted promotional marketing strategies that enhance brand association which will have a large impact on brand equity. Hypothesis 3: The brand loyalty of the Office of the Tax Ombud, which is associated with fairness, will have positive and significant impact on brand equity.The relationship between brand loyalty and brand equity was found to be positively strong and significant. The results indicate that brand loyalty drives brand equity and therefore supports Hypothesis 3. Therefore, brand loyalty should be a priority when the Office of the Tax Ombud implements marketing strategies that will allow consumers to use its services and promote its brand equity. Hypothesis4: Perceived quality of the Office of the Tax Ombud will have a positive and significant impact on brand equity. The results showed that perceived quality is an important dimension of brand equity as it displayed a strong, perfect positive relationship. Perceived quality is seen as an important aspect of building strong service brands (Balaji, 2011) and is also strongest when compared to other dimensions. Furthermore, the significance of perceived quality is viewed as important by respondents which can be attributed to the loyal consumers who are familiar with the brand, and have experienced the quality service of the Office of the Tax Ombud; hence they view it as high. This confirms Aaker’s (1991) suggestion that perceived quality has a strong influence on brand loyalty and confirms its competitive advantage in improving quality of service as a key strategic issue for organisations within the service sector (Esmaeilpour, Mohamadi, & Rajabi, 2011). It is therefore important that the Office of the Tax Ombud continues to focus on brand strategies that enhance customer experience and activities that promote its quality of service since it has the strongest impact on brand equity. The results of the study suggest that consumer based brand equity plays an important role in the service environment where the branding and marketing managers can continuously use the results to solicit feedback from consumers to promote its services. The Office of the Tax Ombud, being a beckon of hope for taxpayers who don’t trust the tax administration system and have been treated unfairly by South African Revenue Services, can implement marketing activities that build and strengthen its brand and promote its services, and continues to be the office which is a bastion of fairness and honesty. In conclusion, the findings indicated that among the brand equity determinants, the most influential was to be perceived quality and it has the strongest relationship, which is positive and statistically significant. This was closely followed by brand loyalty and then brand association. These determinants had a positive impact on brand equity and were significant predictors of brand equity. On the other hand, brand awareness was not significant in predicting brand equity. This can be due to the fact that consumers might be aware, but have not had cause to use the services of the Office of the Tax Ombud. In addition, the results further displayed that consumer based brand equity can be used in the service industry for institutions like the Office of the Tax Ombud, as a tool to assist in formulating marketing and communications activities that can build its brand equity. Future research could look at brand equity in the service environment with more emphasis on quality and brand equity within the ombud sector as their services are expected to make a difference in consumers’ perceptions of the organisation. Such research could also be used to gauge how consumers perceive the service environment, provide more insightful information on how best ombuds can use brand equity to promote awareness, association, loyalty, and perceived quality, and therefore drive a proper consumerbased brand approach model. It is proposed that a qualitative survey be undertaken to gain more insight into some of the findings.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters in Management in the field of Strategic Marketing, Johannesburg, 2019
Keywords: Branding (Marketing)--South Africa; Ombudspersons; Brand name products